The role of tissue biopsy as a biomarker in REM sleep behavior disorder. (June 2020) - Zitser, Jennifer; Gibbons, Christopher; Miglis, Mitchell G.
Summary: Patients with idiopathic REM-sleep behavior disorder (iRBD) are at substantial risk of progressive neurodegenerative disease of α-synuclein pathology. Longitudinal studies have demonstrated that abnormal α-synuclein deposition occurs early in the course of disease and may precede the appearance of motor symptoms by several decades. This provides rationale for the use of a reliable biomarker to both follow disease progression and to assess treatment response, once disease-modifying treatments become available. Tissue α-synuclein has emerged as a promising candidate, however the utility of α-synuclein detection in tissues accessible to biopsy in iRBD remains unclear. This article summarizes the current literature on the role of tissue biopsy in iRBD, with specific focus on its potential role as a biomarker of disease progression and its role in future clinical trials. Highlights: Tissue biopsy provides a minimally invasive in-vivo assay of α-syn deposition that can be followed over time. Longitudinal studies are needed to assess the relationship between pattern and density of α-synunclein tissue deposition and the association between type and severity of central nervous system disease. The choice of α-synuclein analysis technique is important for sensitivity and specificity of results. Tissue biopsy has become increasingly less invasive over time, with skin now providing a readily accessible and reliable tissue for analysis.